Coulometric response of solid-contact anion-sensitive electrodes. (20th January 2021) - Han, Tingting; Mattinen, Ulriika; Mousavi, Zekra; Bobacka, Johan
Research highlights: The coulometric transduction of solid-contact anion-sensors is explored. The anion sensors show fast charge transfer and ion transport properties. The anion sensors are suitable for coulometric sensing. Coulometry allows amplification of the analytical signal of the anion sensors. Abstract: In this work, the coulometric response of nitrate, perchlorate, and sulfate solid-contact anion-sensitive electrodes was investigated. The coulometric transduction method was originally introduced and so far mainly studied for solid-contact cation-selective sensors using poly(3, 4-ethylenedioxythiophene) (PEDOT) doped with poly(styrene sulfonate) as transducer. Here we provide additional proof-of-concept for the coulometric transduction method by focusing on the electrochemical characteristics of anion sensors. PEDOT was electrodeposited in the presence of small anions, including chloride, nitrate, sulfate, and perchlorate. The counterion was found to influence the yield of electroactive PEDOT, which is an important parameter for the coulometric response. Anion-sensitive electrodes were prepared by coating the PEDOT solid contact with plasticized PVC-based anion-sensitive membranes by drop-casting or spin-coating. The influence of the thickness of the PEDOT film and the anion-sensitive membrane on the coulometric response was studied in detail. The solid-contact anion sensors showed fast charge transfer and ion transport properties, making them suitable for coulometric sensing. Also for anion-sensitive electrodes, the analytical signal was amplified by increasing the thickness of the PEDOT solid contact, which is fully consistent with earlier works on cation-selective electrodes. This work shows that the coulometric transduction principle is feasible and robust for various types of solid-contact ISEs.